The College cookbook : 100+ fast, fresh, easy & cheap recipes - Pick, Aubrie (San Francisco, CA : Weldon Owen, 2018)
The cookbook that every student going off to college needs! Simple and delicious, easy-to-follow, few ingredient, cost- and time-efficient recipes for college students with no time, no money, and limited knowledge of how to cook for themselves. Think outside of the (mac & cheese) box! Eating on a budget and with no time to cook doesn't mean one can't eat well. With this collection of quick and easy recipes, college students and other time-challenged, budget-conscious cooks can easily prepare low-cost, fresh-tasting dishes, whether they have access to a kitchen or are limited to the dorm kitchenette. Step-by-step, no-fail, fresh and delicious recipes include make-ahead tips, shopping lists, and cooking time for easy reference. Lots of simple tips for stretching easy preparations to many meals. Instagram-worthy photos and lots of fun graphics offer inspiration.
Cover title.
Description based on print version record.
Keywords: Quick and easy cooking; Cuisine rapide; COOKING -- Methods -- Cookery for One; COOKING -- Methods -- Low Budget; COOKING -- Methods -- Quick & Easy; Quick and easy cooking; Cookbook; Wellness resources; cookbooks; Cookbooks; Cookbooks; Livres de cuisine